Kisspeptin1 modulates odorant‐evoked fear response via two serotonin receptor subtypes (5‐HT1A and 5‐HT2) in zebrafish. (17th April 2015) - Nathan, Fatima M.; Ogawa, Satoshi; Parhar, Ishwar S.
Abstract Kiss1, a neuropeptide predominantly expressed in the habenula, modulates the serotonin (5‐HT) system to decrease odorant cue [alarm substance (AS)]‐evoked fear behaviour in the zebrafish. The purpose of this study was to assess the interaction of Kiss1 with the 5‐HT system as well as to determine the involvement of the 5‐HT receptor subtypes in AS‐evoked fear. We utilized 0. 28 mg/kg WAY 100635 (WAY), a selective 5‐HT1A receptor antagonist, to observe the effects of Kiss1 administration on AS‐evoked fear. We found WAY significantly inhibited the anxiolytic effects of Kiss1 (p < 0.001) with an exception of freezing behaviour. Based on this, we utilized 92.79 mg/kg methysergide, a 5‐HT1 and 5‐HT2 receptor antagonist, and found that methysergide significantly blocked the anxiolytic effects of Kiss1 in the presence of the AS (p < 0.001). From this, we conclude that Kiss1 modulates AS‐evoked fear responses mediated by the 5‐HT1A and 5‐HT2 receptors. Kiss1 peptide intracranially (IC) administrated has been shown to decrease olfactory, alarm substance (AS)‐evoked fear response. Blockade of the 5‐HT1A receptor utilizing WAY 100635 (0.28 mg/kg) and the 5‐HT1 and 5‐HT2 receptor utilizing methysergide (92.79 mg/kg) produced increased AS‐evoked fear responses that were unable to be overcome even during the recovery period. Blockade of this 5‐HT system followed by Kiss1 administration showed that the peptide was unable to recover the anxiolytic effects upon 5‐HT1A blocking using WAY 100635 with the exception of freezing behaviour while methysergide significantly blocked all the anxiolytic effects of Kiss1. These findings implicate that Kiss1 could modulate AS‐evoked fear responses mediated by 5‐HT1A and 5‐HT2 receptors.